The Effect of Interactive Learning Media Assisted Deep Learning Approach on the Learning Outcomes of Grade VIII Metthayom Students at Ban Mapring School, Yaring, Pattani Province, Thailand - Nurma Sari Siregar; Jalilah Azizah Lubis; Melvariani Syari Batubara; Mutiara Yamu; Fitri Agustina Lubis (Postgraduate, University of Mataram, 2026)
This study aims to evaluate the impact of the implementation of immersive learning strategies with the help of interactive learning resources on the academic performance of eighth-grade students of Metthayom at Ban Mapring School, Yaring, Pattani Province, Thailand. The method applied was a quasi-experimental design involving a control group and a treatment group. Data collection was carried out through a learning outcome test designed based on competency indicators, then analyzed using descriptive and inferential statistics. The findings of the study revealed that students in the treatment group who received immersive learning supported by interactive media showed significantly better learning outcomes compared to the control group. This indicates that the application of animation, visualization, and two-way communication in the learning process can increase active participation, conceptual understanding, and critical and reflective thinking skills among students. The discussion shows that the integration of immersive learning strategies with interactive learning resources can create a much more meaningful and efficient learning experience in helping students apply concepts more deeply. In conclusion, the use of immersive learning strategies accompanied by interactive learning resources has a positive and significant impact on improving student learning outcomes, so it is worth considering as an innovative alternative in the learning process.